2015
DOI: 10.1038/mp.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

Neurexin 1 (NRXN1) splice isoform expression during human neocortical development and aging

Abstract: Neurexin 1 (NRXN1), a presynaptic adhesion molecule, is implicated in several neurodevelopmental disorders characterized by synaptic dysfunction including, autism, intellectual disability, and schizophrenia. To gain insight into NRXN1’s involvement in human cortical development we used quantitative real time PCR to examine the expression trajectories of NRXN1, and its predominant isoforms NRXN1-α and NRXN1-β in prefrontal cortex from fetal stages to aging. Additionally, we investigated whether prefrontal corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…NRXN1 has been implicated in neocortical development and aging [23], and NRXN1 genetic variations affect the risk of autism and schizophrenia [28, 29]. Of note, we reported the locus including NRXN1 already in our previous work highlighting novel suggestive loci for FTD in the Italian population [3]; here, we provide further support for this association and expand on its potential implication in driving AAO.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…NRXN1 has been implicated in neocortical development and aging [23], and NRXN1 genetic variations affect the risk of autism and schizophrenia [28, 29]. Of note, we reported the locus including NRXN1 already in our previous work highlighting novel suggestive loci for FTD in the Italian population [3]; here, we provide further support for this association and expand on its potential implication in driving AAO.…”
Section: Discussionsupporting
confidence: 80%
“…Considering the 6 loci that we identified influencing AAO in FTD, the literature suggests, particularly for NRXN, HPCAL1 , and PTPRD , a direct link with the biology of the brain through calcium-mediated neuronal signaling, development of neocortical regions as well as axonal myelination and glutamatergic/GABAergic synapsis, respectively [2326]. It is interesting to gather that variability in these genes, and their associated functions and processes, could underpin the modulation of disease onset in FTD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcripts of these 108 genes show elevated expression patterns in fetal brain when compared to post-natal brain [16]. Similar studies have reported increased expression of schizophrenia risk genes during early brain development [17, 18]. These findings are consistent with a generalized neurodevelopmental role for many genes associated with risk of schizophrenia.…”
Section: Genetics and Epigenetics Of Schizophreniasupporting
confidence: 78%
“…Full details of the postmortem human brain collection used in the current study have been previously described (25). Additional information regarding tissue collection is provided in the data supplement accompanying the online version of this article.…”
Section: Methodsmentioning
confidence: 99%